In search of meaningful participation: Making connections between emotions and learning. (May 2021) - Frankel, Sam; Mountford, Mackenzie
Abstract: Research on participation has advanced our understanding of children's everyday lives by increasingly bringing into focus what society perceives as 'meaningful'. This piece is driven by a desire to extend this investigation by sharing a creative research journey. Here, we have combined our theoretical musings, initial conversations with children, and evolving methodological approaches to show how our research approach has changed as we seek meaningful ways to involve children. Accordingly, this paper highlights the positive consequences of a reflective research process that focuses on children's emotions as we consider children's capacities as learners. We argue that by critically engaging with what is meaningful in the context of participation, we can demonstrate the value of children's voices, challenging dominant discourses about children's competence. Highlights: Traditional understandings of children's competence have marginalised their participation in the research process. Exploring children's feelings about participation enables adults to co-create meaningful participatory opportunities. Children's sense of belonging defines the extent to which they find participation meaningful. Researchers can amplify children's voices by prioritising a shared research agenda. Emotions and learning should be connected to facilitate meaningful participation, benefitting adults and children.